Work-based learning in tertiary education in Europe - examples from six educational systems : part II - case studies - Hippach-Schneider, Ute [Verfasser]; Schneider, Verena [Verfasser] (Bundesinstitut für Berufsbildung, 2018)
"The implementation of work-based learning elements in programmes of tertiary education can be seen as a trend of the last years. Different models and approaches have been developed. In the context of a BIBB-research project, examples in England, France, Ireland, Norway, Austria and Poland have been investigated, analysed and thus the great variety of practice-oriented and practice-integrated programmes disclosed. Interviews with representatives from research, education policy administration but also with students, companies and education institutions provide an insight in concrete experience and appraisal of selected education programmes. In all, the project as well as this publication have had the goal to contribute to a better visibility of vocational/professional education at tertiary level and facilitate a more critical debate about the issue of an increasing academisation." (Authors' abstract, BIBB-Doku)
Keywords: S System beruflicher Bildung; L 2.1.3 Erfahrungslernen; T 1.5 International vergleichende Berufsbildungsforschung; I 2.2 Europa; Höhere Berufsbildung; Lernen am Arbeitsplatz; Internationaler Vergleich; Fallstudie; England; Frankreich; Irland; Norwegen; Österreich; Polen